The Teacher's Problem in Planning English Speaking - Dinda Gustiana; Najwa Alzuhda Sitorus; Qorri Fadhilah; Siti Sholikah; Yulia Hidayat (GLOBAL SCIENTS PUBLISHER, 2025)
Lesson planning is a critical component of the teaching process, particularly in English-speaking lessons. This study aims to investigate the challenges faced by junior high school teachers in planning effective English-speaking lessons. Using a qualitative case study approach, data were collected through in-depth interviews with English teachers in Medan. Findings reveal that teachers encounter several obstacles, including difficulties in designing materials that accommodate diverse student abilities, limited resources, ineffective time management, and low student motivation. Additionally, speaking skill evaluations tend to emphasize fluency and pronunciation, neglecting aspects like creativity and confidence. The study recommends adopting student-centered approaches, such as project-based learning, improved time management strategies, and interactive teaching methods to address these challenges. A holistic evaluation framework is also suggested to assess broader aspects of speaking skills. This research provides practical insights for educators and policymakers to enhance the quality of English-speaking instruction in schools.